Citrus - Albrigo, Leo Gene, 1940- (Crop production science in horticulture., 2019)
This second edition of Citrus, like the original by F.S. Davies and L.G. Albrigo, intends to provide the reader with an updated overview of citriculture from a worldwide perspective. Current theories and technological advances in citriculture are emphasized, citing specific examples of how and where they are used. The text begins with a discussion of major production areas with figures and current trends (Chapter 1). The confusing and controversial taxonomic situation for Citrus and related genera is then discussed, emphasizing molecular biology (biotechnological) advances that are clarifying the genetic relationships between various citrus species. This is followed by a discussion of the major commercially important citrus species and cultivars and traditional and current techniques in citrus breeding (Chapter 2). Chapter 3 covers the importance of rootstocks in citriculture and discusses the major rootstocks, their advantages and disadvantages. In Chapter 4, the role of climatic factors in worldwide citrus production is emphasized, including their effects on citrus yields, growth, economic returns and fruit quality. Plant husbandry, including nursery practices, irrigation, fertilizer application, freeze protection, pruning, growth regulator use and weed control is covered in Chapter 5. In Chapter 6, the major pests and recent changes in their distribution are covered. Diseases of citrus, emphasizing major problems and control measures are the topic of Chapter 7. The final chapter (8) deals with postharvest quality, harvesting and handling of citrus fruits, including the importance of biotic and abiotic problems, as well as packinghouse and processing techniques.